Fe2(SO4)3 + 3Ba(NO3)2 = 2Fe(NO3)3 + 3BaSO4
2Fe(+3) + 3SO4(-2) + 3Ba(+2) + 6NO3(-) = 2Fe(+3) + 6NO3(-) + 3BaSO4
3Ba(+2) + 3SO4(-2) = 3BaSO4
Fe2(SO4)3 + 6NaOH =2 Fe(OH)3 + 3Na2SO4
2Fe(+3) + 3SO4(-2) + 6Na(+) + 6OH(-) = 2Fe(OH)3 + 6Na(+) + 3SO4(-2)
2Fe(+3) + 6OH(-) = 2Fe(OH)3
2Fe(OH)3 = Fe2O3 + 3H2O
Fe2O3 + 6HCl = 2FeCl3 +3 H2O
Fe2O3 + 6H(+) + 6Cl(-) = 2Fe(+3) + 6Cl(-) + 3H2O
Fe2O3 + 6H(+) = 2Fe(+3) + 3H2O
Fe2(SO4)3 +3CaCl2 = 2FeCl3 + 3CaSO4
2Fe(+3) + 3SO4(-2) + 3Ca(+2) + 6Cl(-) = 2Fe(+3) + 6Cl(-) + 3CaSO4
3Ca(+2) + 3SO4(-2) = 3CaSO4
3NaOH + FeCl3 = Fe(OH)3 + 3NaCl
3Na(+) + 3OH(-) + Fe(+3) + 3Cl(-) = Fe(OH)3 + 3Na(+) + 3Cl(-)
Fe(+3) + 3OH(-) = Fe(OH)3
ZnSO4 + 2KOH = Zn(OH)2 + K2SO4
Zn(+2) + SO4(-2) + 2K(+) + 2OH(-) = Zn(OH)2 + 2K(+) + SO4(-2)
Zn(+2) + 2OH(-) = Zn(OH)2
Na2CO3 + 2HNO3 = 2NaNO3 + CO2 + H2O
2Na(+) + CO3(-2) + 2H(+) + 2NO3(-) = 2Na(+) + 2NO3(-) + CO2 + H2O
CO3(-2) + 2H(+) = CO2 + H2O
CuO + 2HCl = CuCl2 + H2O
CuO + 2H(+) + 2Cl(-) = Cu(+2) + 2Cl(-) + H2O
CuO + 2H(+) = Cu(+2) + H2O
2) AlCl3 + 3NaOH = Al(OH)3 + 3NaCl
Al(+3) + 3Cl(-) + 3Na(+) + 3OH(-) = Al(OH)3 + 3Na(+) + 3Cl(-)
Al(+3) + 3OH(-) = Al(OH)3
2Al(OH)3 + 3H2SO4 = Al2(SO4)3 + 6H2O
2Al(OH)3 + 6H(+) + 3SO4(-2) = 2Al(+3) + 3SO4(-2) + 6H2O
2Al(OH)3 + 6H(+) = 2Al(+3) + 6H2O
K2CO3+H2SO4=H2O+CO2(газ)+K2SO4. Я бы решила тебе эту задачу, но лень)